СПІВПРАЦЯ ПЕДАГОГА ТА БАТЬКІВ У ПЕРІОД АДАПТАЦІЇ ДИТИНИ ДО ДОШКІЛЬНОГО ЗАКЛАДУ (Педагогіка вищої та середньої школи, 2009)
This article describes the problem of contribution between the educator and parents in the period of child's adaptation to preschool establishment characterizes the variety of forms interactions of the preschool establishment with the family.